(untitled) (Research, Society and Development, 2022)
This work evaluates the enzymatic production of hydrolases and oxireductases by endophytic fungi isolated from leaves of the caesarweed (Urena lobata L.), which is a perennial plant that is well adapted to the Amazon floodplains region, being and is widely used in the production of hessian sacks and other products of natural fiber. Fungi strains Fusarium sp. (1290) and Corynespora sp. (1291) were reactivated, and had their DNA extracted and sequenced to obtain molecular identification. For enzymatic production, dried and ground caesarweed was used as a substrate in the mineral salt solutions Manachini and GLBN 40 over during 10 days of submerged cultivation (CS) under agitation. The CA was vacuum filtered daily with a 0.22 µm Millipore membrane to obtain enzymatic extracts, from which the activities of FPase, xylanase, CMCase, β-glycosidase, pectinase, laccase, manganese peroxidase (MnP) and lignin peroxidase (LiP) were evaluated. Lines strains 1290 and 1291 were identified as F. pseudocircinatum and C. torulosa, respectively, the latter being the best producer of laccase (8,691 U/L), MnP (5,353 U/L), β-glycosidase (0.328 U/mL) and CMCase (0.351 U/mL) and the fungus F. pseudocircinatum was the best producer of FPase (1.294 U/mL), xylanase (12.052 U/mL) and pectinase (0.183 U/mL). No LiP activity was detected for either of the strains. The results showed that the strains used are promising for the production of seven of the eight quantified enzymes, and these enzymes are of interest to several industrial sectors.